Deconstruction: Overview and Critique: النظرية التفكيكية: عرض ونقد - Bakour, Bachar (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Deconstruction is a post-structuralist, intellectual, and critical theory, formulated by the French philosopher Jacques Derrida in the 1960s. It is an approach to re-reading literary and philosophical given their multiple possible meanings. This article seeks to present a brief account of deconstruction: its epistemological roots of Nietzsche and Martin Heidegger, major concepts, tools. Then, it presents a critique of deconstruction, especially in the works of John Ellis and Abdel Aziz Hammouda. Furthermore, the article briefly refers to the impact of the deconstruction on the religious text (the Holy Qur'an and the Prophet's Sunnah), as some Arab secularists have laid particular stress on the application of this Western hermeneutics to Islamic texts. For them, it is deemed as a necessary step to ensure that the religious text remains open to many interpretations, and responds to different circumstances and conditions. The article argues that deconstruction, as a literary philosophical doctrine, has been born of Western modernity. And therefore, it does not seem appropriate to transform it into a civilization with different cultural and religious components. النظرية التفكيكية اتجاه فكري ونقدي ولد في عالم ما بعد البنيوية على يد الفيلسوف الفرنسي جاك دريدا. وتمثل هذه النظرية رؤية نقدية تقوم على الهدم والبناء من خلال إعادة قراءة النصوص الأدبية والفلسفية والدينية...إلخ. تسعى هذه المقالة إلى عرض موجز للتفكيكية: الخلفيات المعرفية المستمدة من نيتشة ومارتن هايدجر، وأهم مفاهيمها ومصطلحاتها وأدواتها، ثم بيان أهم الانتقادات العلمية الموجهة ضد هذه النظرية، خصوصاً فيما كتبه جون إليس، وعبد العزيز حمودة. ثم تشير المقالة بإيجاز إلى أثر التفكيكية في اختراق النص الديني: القرآن الكريم والسنة النبوية، على يد العلمانيين العرب الذين ما برحوا يؤكدون على ضرورة تطبيق أمثال هذه الأسس التأويلية الغربية (الهرمنيوطيقا) على النصوص الإسلامية. وبهذا يبقى النص الديني مفتوحاً ومتعدداً بتعدد القراء، وباختلاف الظروف والأحوال. وترى المقالة أن النظرية التفكيكية مجرد مذهب أدبي فلسفي نشأ في الواقع الحداثي الغربي في صراعه مع الدين، يهدف إلى نزع المقدسات، وهدم التقاليد، وزحزحة الأفكار الموروثة عن العلاقة واللغة والنص والسياق والمؤلف والقارئ ودور التاريخ وعملية التفسير. ولا يصح بحال إسقاط هذا المذهب على واقع فكري وثقافي مباين في سياقاته وظروفه لبيئة هذا المذهب.